Protocol for fabricating elastomeric stencils for patterned stem cell differentiation - Stefanie Lehr; Jack Merrin; Monika Kulig; Thomas George Minchington; Anna Kicheva (STAR Protocols)
Summary: Geometrically controlled stem cell differentiation promotes reproducible pattern formation. Here, we present a protocol to fabricate elastomeric stencils for patterned stem cell differentiation. We describe procedures for using photolithography to produce molds, followed by molding polydimethylsiloxane (PDMS) to obtain stencils with through holes. We then provide instructions for culturing cells on stencils and, finally, removing stencils to allow colony growth and cell migration. This approach yields reproducible two-dimensional organoids tailored for quantitative studies of growth and pattern formation.For complete details on the use and execution of this protocol, please refer to Lehr et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.